The Digital Literacy of Lecturers during the COVID-19 Pandemic - Solihin, Muhtar Mochamad (Jurnal Pekommas, 2022)
The learning conditions due to the current COVID-19 pandemic require lecturers to have good digital literacy skills. The aims of this study were to: 1) describe the tools and applications used by lecturers in online learning, 2) describe digital literacy of lecturers, and 3) analyze factors related to digital literacy. This research approach uses a quantitative survey method with 49 lecturers at one of the largest Islamic religious campuses in Indonesia. The results of this study indicate that: 1) the tools used by lecturers in online learning during the COVID-19 pandemic consist of internet-connected laptops (63.27 percent), internet-connected smartphone devices (30.61 percent), internet-connected computers (4.08 percent) , and a small percentage (2.04 percent) use internet-connected gadgets or tablets. Applications used by lecturers in learning consist of Zoom (95.92 percent), WhatsApps (89.90 percent), Google Classroom (57.14 percent) and Academic Information System or AIS (55.10 percent). 2) The lecturer's digital literacy level (63.27 percent) is in the moderate category which tends to be high with a score between 94 to 112 (94 ≤ X < 113). 3). The factor that is significantly related to the lecturer's digital literacy level is the respondent's basic income.